Comparison Between the Provision of White Ambon Banana Fruit and Red Dragon Fruit on Hemoglobin Levels - Elis Muliawati; Bunga Tiara Carolin; Nurul Husnul Lail (Nursing and Health Sciences Journal (NHSJ), 2022)
Anemia is a factor in maternal mortality in 2020 in South Tangerang City, 48.8%. One of them is iron foods, namely white Ambon banana fruit juice and red dragon fruit. Rawa Buntu Health Center's incidence of anemia in pregnant women is relatively high. They know the comparison between the administration of white Ambon banana juice and red dragon fruit juice on the hemoglobin levels of pregnant women in the third trimester. This quasi-experimental research design used a two-group pretest and posttest design. The research sample amounted to 34 respondents, consisting of 17 respondents, using a purposive sampling technique. Data were analyzed using paired t-test and an Independent t-test. Research results: In univariate analysis, the difference in the average Hb levels of white Ambon banana juice was 2.48, and that of red dragon fruit juice was 1.80. The results of the bivariate analysis with a significance value of 0.000. giving Ambon banana juice increased Hb levels of pregnant women higher than giving red dragon fruit juice. Pregnant women are expected to be diligent in consuming foods containing iron, white Ambon banana juice, and red dragon fruit juice to increase Hb levels in the mother's blood.